Eosinophils mitigate intestinal fibrosis while promoting inflammation in a chronic DSS colitis model and co-culture model with fibroblasts - Inge Jacobs; Sara Deleu; Bo-Jun Ke; Jonathan Cremer; Ellen Dilissen; Gert De Hertogh; Tobie Martens; Pieter Vanden Berghe; Gianluca Matteoli; Séverine Vermeire; Christine Breynaert; Tim Vanuytsel; et al. (Scientific Reports)
Abstract Eosinophils were previously reported to play a role in intestinal inflammation and fibrosis. Whether this is as a bystander or as an active participant is still up for debate. Moreover, data describing a causal relationship between eosinophils and intestinal fibrosis are scarce. We here aimed to elucidate the role of eosinophils in the pathogenesis of intestinal inflammation and fibrosis. Therefore, we stimulated fibroblasts with (active) eosinophils or with Eosinophil Cationic Protein (ECP), and assessed fibroblast activation via flow cytometry and immunocytochemistry. We observed decreased fibroblast activation when fibroblasts were co-cultured with active eosinophils or after stimulation with ECP in comparison to monoculture conditions, but not in case of co-culturing with inactivated eosinophils. Furthermore, eosinophil depletion in a RAG−/− chronic DSS colitis model resulted in decreased inflammation, but increased development of fibrosis. In this model, we could show increased expression of the anti-inflammatory protein IL-10 and the pro-fibrotic factors IL-1β, FGF-21 and TGF-β3 in the eosinophil-depleted mice compared to the control mice. In conclusion, our in vitro data revealed an anti-fibrotic role for eosinophils. In line, in a chronic murine colitis model, we observed a pro-inflammatory, but an anti-fibrotic, role for eosinophils. Furthermore, we identified an increased presence of anti-inflammatory and pro-fibrotic cytokines in the eosinophil depleted group.